The Concept of Distance in International Business Research: A Review and Research Agenda. (23rd April 2015) - Hutzschenreuter, Thomas; Kleindienst, Ingo; Lange, Sandra
Abstract : This paper reviews the literature on the effects of distance arising from country differences on outcomes at the firm and subsidiary level. It provides some clarity on what has been learned so far about distance by answering four questions: Which distance? Why does distance matter? What outcomes are affected by distance? and What aggravates or alleviates the effects of distance? Based on the review of the literature, a set of future research suggestions are developed, intended to direct attention to research questions that the authors believe are among the most pressing questions in distance research and that may have the potential to advance the field substantially.